Biochemical analyses demonstrate that Bt maize has no adverse effects on Eisenia fetida. - Fengci Wu; Zhilei Jiang; Baifeng Wang; Junqi Yin; Daming Wang; Xinyuan Song (PLoS ONE, 2022)
The potential effects of Bt (Bacillus thuringiensis) maize on non-target organisms should be evaluated before such maize is commercially planted. Earthworms play an indispensable role in the soil ecosystem; act as important bio-indicators of soil quality and environmental pollution. Therefore, earthworms are often used as the object to evaluate the non-target effect of Bt maize. To accelerate the commercialization of transgenic maize in China, a 90-day Eisenia fetida feeding experiment was conducted to evaluate the potential effects of Bt maize line, BT799-which was developed by China Agricultural University and contains the Cry1Ac gene-and its non-Bt conventional isoline-Zheng 58-on E. fetida. Our results showed that the Bt maize line had no significant effects on the growth, reproduction, or enzymatic activities of these earthworms. In summary, Bt maize had no toxic effects on E. fetida.